2011
DOI: 10.1007/s00213-011-2373-6
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline as a smoking cessation aid in schizophrenia: effects on smoking behavior and reward sensitivity

Abstract: Rationale Smoking rates are up to five times higher in people with schizophrenia than in the general population, placing these individuals at high risk for smoking-related health problems. Varenicline, an α4β2 nicotinic acetylcholine receptor partial agonist, is a promising aid for smoking cessation in this population. To optimize benefits to risks of treatment, it is critical to identify reliable predictors of positive response to varenicline in smokers with schizophrenia. Objectives Negative symptoms of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 67 publications
1
21
1
1
Order By: Relevance
“…A recent study found that maintenance therapy with varenicline prolonged tobacco abstinence rates in patients with schizophrenia (Evins et al, 2014). Moreover, schizophrenia patients with lower baseline symptoms of affective flattening were more likely to achieve smoking abstinence and demonstrated larger increases in reward sensitivity during varenicline treatment (Dutra et al, 2012). Table 3 depicts the results of clinical trials of nAChR agonists and PAMs in patients with schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that maintenance therapy with varenicline prolonged tobacco abstinence rates in patients with schizophrenia (Evins et al, 2014). Moreover, schizophrenia patients with lower baseline symptoms of affective flattening were more likely to achieve smoking abstinence and demonstrated larger increases in reward sensitivity during varenicline treatment (Dutra et al, 2012). Table 3 depicts the results of clinical trials of nAChR agonists and PAMs in patients with schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies indicate that varenicline potently and selectively interacts at ␣4␤2* nAChRs (Mihalak et al, 2006;Rollema et al, 2007;Reperant et al, 2010;Brandon et al, 2011;Maloku et al, 2011;Dutra et al, 2012;Lotfipour et al, 2012;Shim et al, 2012). In fact, it has been suggested that varenicline exerts its beneficial effects as a smoking cessation aid by targeting this nAChR population.…”
Section: Discussionmentioning
confidence: 99%
“…Although smoking cessation is clearly an option, most smoking cessation programs yield only a 12–15% abstinence rate at 1 year [32,33,34]. In fact, the common smoking cessation treatment, varenicline (trade name: Chantix), has been shown to exacerbate psychotic symptoms [35], although this may be related to severity of negative symptoms in that particular individual [36], and other studies have shown that varenicline may actually be efficacious for smoking cessation in schizophrenia [37,38]. …”
Section: Schizophrenia and Tobacco Dependencementioning
confidence: 99%